2018
DOI: 10.15578/iaj.13.1.2018.41-49
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Life Cycle of Marine Leech Isolated From Cultured Hybrid Grouper in the Northern Bali Waters of Indonesia

Abstract: The aims of this study were to identify and to determine life cycle of marine leech isolated from cultured hybrid grouper “cantik” (Epinephelus fuscoguttatus fx E. polyphekadion m) in the northern Bali waters of Indonesia under laboratory conditions. Observation of the life cycle of the marine leech was done using petri-dishes (9 cm in diameter) arranged into two groups. In group-1, a petri-dish was filled with sterile seawater (with water exchange of 50%-60% every two days) and in group-2, a petri-dish was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
3
9
0
1
Order By: Relevance
“…The marine ectoparasite was mostly found attached to the body surface, eyes, mouth, ventral fins and dorsal fins. These results were very similar with previous studies in the same species (Azmey, Taruna, Taha, & Arai, 2020; Jamaris, Roza, & Mahardika, 2019; Mahardika, Mastuti, Sudewi, et al, 2018; Murwantoko et al, 2018) or different fish species (Azuar, Raza'i, & Miranti, 2019; Nagasawa, Shimadzu, & Ikeda, 2012; Nagasawa & Uyeno, 2009; Ravi & Shariman Yahaya, 2017). Accordingly, a study by Cruz‐Lacierda et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The marine ectoparasite was mostly found attached to the body surface, eyes, mouth, ventral fins and dorsal fins. These results were very similar with previous studies in the same species (Azmey, Taruna, Taha, & Arai, 2020; Jamaris, Roza, & Mahardika, 2019; Mahardika, Mastuti, Sudewi, et al, 2018; Murwantoko et al, 2018) or different fish species (Azuar, Raza'i, & Miranti, 2019; Nagasawa, Shimadzu, & Ikeda, 2012; Nagasawa & Uyeno, 2009; Ravi & Shariman Yahaya, 2017). Accordingly, a study by Cruz‐Lacierda et al.…”
Section: Discussionsupporting
confidence: 91%
“…(2008) in several species including brown‐marbled grouper ( Epinephelus fuscoguttatus ), green grouper ( Epinephelus suillus ), humpback grouper ( C. altivelis ), coral grouper ( Epinephelus corallicola ), seabass ( Lates calcarifer ) and snapper ( Lates argentinaculatus ). The next study was reported by Mahardika, Mastuti, Sudewi, and Zafran (2018) infecting hybrid grouper ( Epinephelus fuscogutattus ♀ × Epinephelus lanceolatus ♂) in Gondol, Bali Island (Mahasri, Wulansari, & Imani, 2019), in Situbondo, East Java, Indonesia. The above studies did not provide data on differences in pathogenicity in the different species of groupers, nor did they examine the influence of rearing conditions on the prevalence and intensity of infestation.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Perubahan lingkungan perairan juga berdampak pada kesehatan ikan. Beberapa patogen seperti cacing insang dan lintah Hirudinea dilaporkan menyebabkan kematian massal pada ikan kerapu di Teluk Pegametan [9].…”
Section: Pendahuluanunclassified
“…A marine ectoparasitic fish leech, Z. arugamensis de Silva, 1963, which was first identified in Sri Lanka and belongs to the family Piscicolidae, can infect several teleost fish, including cultured groupers [ 12 , 13 , 14 , 15 , 16 ], by feeding on the blood of its hosts; no other marine leech species has been reported to infest groupers. However, recently, this taxonomic name has been revised to P. arugamensis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%